Intracellular Monitoring of AS1411 Aptamer by Time-Resolved Microspectrofluorimetry and Fluorescence Imaging - Kočišová, Eva; Praus, Petr; Bok, Jiří; Bonneau, Stéphanie; Sureau, Franck (Journal of fluorescence, 2015)
Time-resolved microspectrofluorimetry and fluorescence microscopy imaging-two complementary fluorescence techniques-provide important information about the intracellular distribution, level of uptake and binding/interactions inside living cell of the labeled molecule of interest. They were employed to monitor the "fate" of AS1411 aptamer labeled by ATTO 425 in human living cells. Confocal microspectrofluorimeter adapted for time-resolved intracellular fluorescence measurements by using a phase-modulation principle with homodyne data acquisition was employed to obtain emission spectra and to determine fluorescence lifetimes in U-87 MG tumor brain cells and Hs68 non-tumor foreskin cells. Acquired spectra from both the intracellular space and the reference solutions were treated to observe the aptamer localization and its interaction with biological structures inside the living cell. The emission spectra and the maximum emission wavelengths coming from the cells are practically identical, however significant lifetime lengthening was observed for tumor cell line in comparison to non-tumor one.
Keywords: Aptamer; nádorové buněčné linie; AS1411 aptamer; fluorescenční spektrometrie; fluorescenční mikroskopie; Intracellular fluorescence; Intracellular Space; Microscopy, Fluorescence; aptamery nukleotidové; Time Factors; Oligodeoxyribonucleotides; Aptamers, Nucleotide; Cell Line, Tumor; Base Sequence; sekvence nukleotidů; Spectrometry, Fluorescence; oligodeoxyribonukleotidy; Humans; Phase-modulation lifetime measurement; časové faktory; intracelulární prostor; Fluorescence microscopy imaging; lidé